Databases and information systems v : selected papers from the Eighth International Baltic Conference, DB&IS 2008 - International Baltic Conference on Databases and Information Systems (8th : 2008 : Tallinn, Estonia); Haav, Hele-Mai; Kalja, Ahto (Amsterdam : IOS Press, 2009)
57